Things Are Changing so Fast: Integrative Technology for Preserving Cognitive Health and Community History. (29th June 2018) - Croff, Raina L; Witter IV, Phelps; Walker, Miya L; Francois, Edline; Quinn, Charlie; Riley, Thomas C; Sharma, Nicole F; Kaye, Jeffrey A
Abstract: Background and Objectives: Multimodal interventions are increasingly targeting multiple cognitive decline risk factors. However, technology remains mostly adjunctive, largely prioritizes age relevancy over cultural relevancy, and often targets individual health without lasting, community-wide deliverables. Meanwhile, African Americans remain overburdened by cognitive risk factors yet underrepresented in cognitive health and technology studies. The Sharing History through Active Reminiscence and Photo-imagery (SHARP) program increases physical, social, and cognitive activity within a culturally meaningful context that produces community deliverables—an oral history archive and cognitive health education. Design and Methods: The SHARP application was tested with 19 African Americans ≥55 years, aiming for an easy, integrative, and culturally meaningful experience. The application guided triads in walks 3 times weekly for 6 months in Portland, Oregon's historically Black neighborhoods; local historical images prompted recorded conversational reminiscence. Focus groups evaluated factors influencing technology acceptance—attitudes about technology, usefulness, usability, and relevance to integrating program goals. Thematic analysis guided qualitative interpretation. Results: Technology acceptance was influenced by group learning, paper-copy replicas for reluctant users, ease of navigation, usefulness for integrating and engaging in health behaviors, relevance to integrating individual benefit and the community priority of preserving history amidst gentrification, and flexibility in how the community uses deliverables. Perceived community benefits sustained acceptance despite intermittent technology failure. Discussion and Implications: We offer applicable considerations for brain health technology design, implementation, and deliverables that integrate modalities, age, and cultural relevance, and individual and community benefit for more meaningful, and thus more motivated community engagement.